2009
DOI: 10.1353/sgo.0.0045
|View full text |Cite
|
Sign up to set email alerts
|

Florida Hurricanes and Damage Costs

Abstract: Florida has been visited by some of the most destructive and devastating hurricanes on record in the United States causing well over $450 billion in damage since the early 20 th century. The value of insured property in Florida against windstorm damage is the highest in the nation and on the rise. The frequency and severity of hurricanes affecting Florida are examined from the best set of available data and the damages are related to characteristics of the storms at landfall. Results show that normalized losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In particular, the 1930s were marked by drought and exceptionally warm maximum and minimum temperatures (Rogers 2013;DeGaetano and Allen 2002), as well as heat waves (Kunkel et al 2013). In addition, the Labor Day hurricane of 1935 devastated the Florida Keys with the lowest recorded pressure of any Florida hurricane at the time (Malmstadt et al 2009), and it was one of only three hurricanes to make landfall at category 5 intensity in the United States since 1851.…”
Section: B Station Datamentioning
confidence: 99%
“…In particular, the 1930s were marked by drought and exceptionally warm maximum and minimum temperatures (Rogers 2013;DeGaetano and Allen 2002), as well as heat waves (Kunkel et al 2013). In addition, the Labor Day hurricane of 1935 devastated the Florida Keys with the lowest recorded pressure of any Florida hurricane at the time (Malmstadt et al 2009), and it was one of only three hurricanes to make landfall at category 5 intensity in the United States since 1851.…”
Section: B Station Datamentioning
confidence: 99%
“…Of all the deaths occurring in the United States attributed to Atlantic tropical cyclones from 1963 to 2012, 49% are caused by storm surge and 8% by wind [ Rappaport , ]. TC events also cause economic losses that can reach beyond billions of dollars [ Pielke et al , ; Malmstadt et al , ]. The nearshore environment for these coastal cities provides vast economic activities, including mineral and petroleum extraction, commercial fishing, port traffic, seafood processing, and marine sports fishing [ Adams et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the U.S. population lives within fifty miles of a coast, and as coastal populations and infrastructure continue to rise, so does the property damage associated with these events (USGS 2005). Economic losses from individual events can reach billions of dollars, and, collectively, these storms have cost well over $450 billion in the United States since the early 20th century (Pielke et al 2008;Malmstadt, Scheitlin, and Elsner 2009). The active season of 2005, with Katrina, Rita, and Wilma, demonstrated that hurricanes can inflict vast amounts of damage, and the need for hurricane research and preparedness has escalated (USGS 2005).…”
mentioning
confidence: 99%